Association between life’s crucial 9 and sarcopenia: estimated glucose disposal rate as a key mediator - Tang, Xialian; Li, Bin; Li, Dexin; Wang, Yingji (Frontiers in Nutrition, 2025)
BackgroundStudies indicate an association between cardiovascular health and sarcopenia (SP). Insulin resistance is significantly linked to both cardiovascular disease and diabetes. The estimated glucose disposal rate (eGDR), a reliable marker of insulin sensitivity, has an unclear relationship with SP, yet it may hold predictive value.MethodsData from 7,769 participants in the U.S. National Health and Nutrition Examination Survey (NHANES) 2011–2018 were analyzed. All analyses incorporated appropriate NHANES sampling weights, primary sampling units (PSUs), and stratification variables to ensure national representativeness and correct variance estimation. Multivariate logistic regression, restricted cubic splines (RCS) with specified knot placement, subgroup analyses with multiple comparison corrections, and mediation analysis were employed to examine the association between LC9 and SP prevalence. Mediation analysis was conducted to evaluate the role of eGDR levels in the LC9-SP relationship.ResultsAmong the 7,769 participants, 647 had sarcopenia. In crude models, each 10-point increase in LC9 was associated with a 4.9% decrease in sarcopenia odds (OR: 0.951, p < 0.001). Similarly, each 1-unit increase in eGDR was associated with a 26.5% decrease in the odds of sarcopenia (OR: 0.735, p < 0.001). However, after adjusting for all covariates including BMI, this association became non-significant (OR: 0.994, p = 0.282). Compared to the lowest tertile, participants in the highest tertiles of LC9 and eGDR had significantly lower odds of SP, with reductions of 83.4% (p < 0.001) and 86.0% (p < 0.001), respectively. RCS and threshold effect analysis revealed a non-linear relationship between LC9 and SP risk, with an inflection point identified at LC9 = 73.33. Mediation analysis indicated that eGDR partially mediated the association between LC9 and SP, accounting for 48.5% of the total effect (p < 0.001).ConclusionIn crude models, an inverse association was observed between LC9 and sarcopenia prevalence in US adults. However, this association became non-significant after full adjustment including BMI. The estimated glucose disposal rate (eGDR) showed statistical mediation of this relationship.